Komparatystyka literacka wobec translatologii. Przegląd stanowisk badawczych - Brzostowska-Tereszkiewicz, Tamara (Przestrzenie Teorii, 2007)
Researches on the previous styles of conducting literary comparative studies on the one hand and on the essentialist source-oriented translatology on the other demonstrate their incommensurability with literary theory discourse and its critical conceptual apparatus. Any interference of their languages representing diverse methodological options has long been precluded. The article includes a brief survey of the historical development and mutual relationships between successive methodological approaches within comparative literature and translatology, from the split between the positivist philology of influences and dependences and hermeneutic translational thought to their final reunion in the culture-oriented Translation Studies of the 1990s. The references to the main trends of the 20th century translatology are supported by their concise characteristics. Translation-oriented comparative literature is viewed as a discipline fit for centering the (post)modern humanities, provided that it will be reoriented in accordance with the main directions of the contemporary theory of literature.